2007
DOI: 10.1007/s00261-007-9240-2
|View full text |Cite
|
Sign up to set email alerts
|

Complications of colonic stenting: a pictorial review

Abstract: Surgical resection of colorectal carcinoma is the only curative treatment currently available. In the elective setting peri-operative mortality is low and refinements in surgical technique and peri-operative care have resulted in high primary anastamosis rates and progressively reduced postoperative morbidity. In those presenting with large bowel obstruction the mortality and morbidity remains high. Many of those undergoing surgery will have incurable disease and a short life expectancy. Increasingly self-expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Tumor overgrowth is the most common cause (Fig. 6), ingrowth through the stent lattice, mucosal prolapse, stent fracture and fecal impaction are less frequent [98,126,131]. In case of stent obstruction due to cancer progression, laser/argon therapy, stent in stent, or surgery can be done [79,127].…”
Section: Complications Of Colonic Stentingmentioning
confidence: 98%
See 2 more Smart Citations
“…Tumor overgrowth is the most common cause (Fig. 6), ingrowth through the stent lattice, mucosal prolapse, stent fracture and fecal impaction are less frequent [98,126,131]. In case of stent obstruction due to cancer progression, laser/argon therapy, stent in stent, or surgery can be done [79,127].…”
Section: Complications Of Colonic Stentingmentioning
confidence: 98%
“…In a systematic review, Khot et al have reported 3 deaths in a total of 565 colonic stent placements; two of them were due to colonic perforation [126]. Colonic perforation is predominantly observed in patients who had balloon dilation of the colonic stenosis or incomplete initial stent deployment [126,130,131]. Risk factors for early perforation following stent insertion are stenosis dilation prior to stent insertion, try to pass the stenosis with the endoscope or excessive manipulation of guide wires, especially in the presence of diverticular disease or early wall ischemia [131].…”
Section: Complications Of Colonic Stentingmentioning
confidence: 98%
See 1 more Smart Citation
“…c perforation, stent migration, stent occlusion, and bleeding have been reported [1, 10,17]. In particular, stent occlusion is seen in around 10-16% of patients and occurs more frequently in palliative settings [1,6,14,20].…”
mentioning
confidence: 99%
“…Additionally, it allows these patients to enjoy the full benefits of minimally invasive surgery [16]. It is a safe procedure with low mortality rates of approximately 1% [1,17]. Various reviews have reported technical and clinical success rates of 75% -100% and 84% -100% respectively [1, 10,18,19].…”
mentioning
confidence: 99%